Potential approaches to prevent hypoglycemia-associated autonomic failure. (14th November 2017) - Lontchi-Yimagou, Eric; You, Jee Young; Carey, Michelle; Gabriely, Ilan; Shamoon, Harry; Hawkins, Meredith
Abstract : Clear health benefits are associated with intensive glucose control in type 1 diabetes mellitus (T1DM). However, maintaining near-normal glycemia remains an elusive goal for many patients, in large part owing to the risk of severe hypoglycemia. In fact, recurrent episodes of hypoglycemia lead to 'hypoglycemia-associated autonomic failure' (HAAF), characterized by defective counter-regulatory responses to hypoglycemia. Extensive studies to understand the mechanisms underlying HAAF have revealed multiple potential etiologies, suggesting various approaches to prevent the development of HAAF. In this review, we present an overview of the literature focused on pharmacological approaches that may prevent the development of HAAF. The purported underlying mechanisms of HAAF include: 1) central mechanisms (opioid receptors, ATP-sensitive K+(KATP ) channels, adrenergic receptors, serotonin selective receptor inhibitors, γ-aminobuyric acid receptors, N-methyl D-aspartate receptors); 2) hormones (cortisol, estrogen, dehydroepiandrosterone (DHEA) or DHEA sulfate, glucagon-like peptide-1) and 3) nutrients (fructose, free fatty acids, ketones), all of which have been studied vis-à-vis their ability to impact the development of HAAF. A careful review of the current literature reveals many promising therapeutic approaches to treat or reduce this important limitation to optimal glycemic control.